2014
DOI: 10.1242/dev.101451
|View full text |Cite
|
Sign up to set email alerts
|

Cell migration: from tissue culture to embryos

Abstract: Cell migration is a fundamental process that occurs during embryo development. Classic studies using in vitro culture systems have been instrumental in dissecting the principles of cell motility and highlighting how cells make use of topographical features of the substrate, cell-cell contacts, and chemical and physical environmental signals to direct their locomotion. Here, we review the guidance principles of in vitro cell locomotion and examine how they control directed cell migration in vivo during developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
119
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(125 citation statements)
references
References 173 publications
(196 reference statements)
1
119
0
2
Order By: Relevance
“…After centrifugation (300 ϫ g for 11 min) at room temperature, the supernatant was removed, and 1 ml of lysis buffer (155 mM NH 4 Cl, 10 mM KHCO 3 , and 0.1 mM EDTA; pH 7.4) was added for 5 min. The suspension was centrifuged at 300 ϫ g for 10 min, and the supernatant was discarded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After centrifugation (300 ϫ g for 11 min) at room temperature, the supernatant was removed, and 1 ml of lysis buffer (155 mM NH 4 Cl, 10 mM KHCO 3 , and 0.1 mM EDTA; pH 7.4) was added for 5 min. The suspension was centrifuged at 300 ϫ g for 10 min, and the supernatant was discarded.…”
Section: Methodsmentioning
confidence: 99%
“…Like most cells, neutrophils and macrophages move on a two-dimensional surface by generating thin membrane protrusions at the front, followed by pulling forward of the cell body and retraction of the back end (1,2), along the lines of the motility model first delineated by Abercrombie et al (3) in the early 1970s (reviewed in Ref. 4). Cells may produce more than one protrusion, but ultimately, the dominant membrane protrusion determines the direction of movement (5).…”
mentioning
confidence: 99%
“…During this process, termed contact guidance, the geometry of the ECM enforces changes to cell morphology and migration direction (Petrie et al ., 2009; Reig et al ., 2014). Classical studies in vivo and in vitro have shown that cells interacting with fibrillar ECM networks exhibit contact guidance (Weiss and Garber, 1952; Dunn and Heath, 1976; Dunn and Ebendal, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Contact guidance where cells utilize anisotropy, often in the form of aligned ECM fibres to orient and migrate along single or multiple fibres is indeed a strong regulator of directed migration that is implicated in numerous developmental, physiologic, and pathophysiologic processes111213. In fact, it is a strong regulator of carcinoma progression14151617.…”
mentioning
confidence: 99%